2020
DOI: 10.3390/ijms21051821
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol S Impaired Human Granulosa Cell Steroidogenesis in Vitro

Abstract: Bisphenol S (BPS) is a structural analog of the endocrine disruptor bisphenol A (BPA); it is the main BPA replacement in the plastics industry. Previous studies have shown that BPA and BPS exhibit similar effects on reproduction in fish and rodent species. BPS reportedly alters steroidogenesis in bovine granulosa cells. Luteinised granulosa cells collected from 59 women who were undergoing an in vitro fertilization procedure were cultured for 48 h in the presence or absence of BPS (10 nM, 100 nM, 1 µM, 10 µM o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 57 publications
2
28
1
Order By: Relevance
“…Isolating/culturing cumulus cells is a valuable complement to our previous experiments since it provides a model where controlled manipulation of cellular functions is possible. In vitro culture of cumulus cells has been extensively utilized in endocrine research as early as 1989 in rats [ 43 ], with particular focus on the effects of reproductive toxicants on these cellular processes [ 12 , 22 , 44 ]. Cumulus cells are quickly being recognized for their importance as experimental models as they offer a non-invasive approach to oocyte quality assessment and prediction of embryonic fates [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Isolating/culturing cumulus cells is a valuable complement to our previous experiments since it provides a model where controlled manipulation of cellular functions is possible. In vitro culture of cumulus cells has been extensively utilized in endocrine research as early as 1989 in rats [ 43 ], with particular focus on the effects of reproductive toxicants on these cellular processes [ 12 , 22 , 44 ]. Cumulus cells are quickly being recognized for their importance as experimental models as they offer a non-invasive approach to oocyte quality assessment and prediction of embryonic fates [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…BPA and BPS very likely have different mechanisms of action and further research is required before an accurate conclusion on BPS safety can be made [ 64 , 65 , 66 ]. Teteau et al [ 12 ] and Amar et al [ 22 ] investigated the mechanism by which BPS can affect sheep and human granulosa cells, respectively. They reported that BPS does not affect cell viability or proliferation, which may explain why we did not see an observable change in flask confluency in the BPS group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In ovines, BPS exposure impairs oocyte development competence with blastocyte rate reduction being observed [ 5 ]. In human granulosa cells, the administration of BPS leads to reduced secretion of oestradiol and progesterone which are observed after 48 h of exposure suggesting that the effects of chronic exposure might be similar [ 6 ]. As BPA crosses the placental barrier, and is known to have an effect on the expression of genes involved with fetal brain development, gene expression in the anterior hypothalamus was studied after exposure in mice highlighting the involvement particularly of genes that are currently thought to be key in Autism Spectrum Disorders [ 7 ].…”
Section: Experimental Studiesmentioning
confidence: 99%